Seroepidemiological surveillance of Burkholderia pseudomallei in Bangladesh - Maude, R; Maude, R; Ghose, A; Amin, MR; Islam, M; Ali, M; Bari, MS; Majumder, M; Wuthiekanan, V; Dondorp, A; Bailey, R; Day, N; et al. (2012)
Melioidosis (. Burkholderia pseudomallei infection) has yet to be demonstrated systematically in Bangladesh. A prospective, cross-sectional serological survey was conducted in 2010 at six Bangladeshi hospitals. Age, gender, occupation and residential address were recorded. Of 1244 patients, 359 (28.9%) were positive for . B. pseudomallei by indirect haemagglutination assay. Farmers had an increased risk of seropositivity (risk ratio. =. 1.4, 95% CI 1.0-1.8; p. =. 0.03). There was no clear geographic clustering of seropositives. Melioidosis should be considered as a possible cause of febrile illness in Bangladesh. Further studies are needed to establish the incidence of clinical disease and distribution of environmental risk. © 2012 Royal Society of Tropical Medicine and Hygiene.